Three-Dimensional Participatory Mapping for Toponymical Name in Nglanggeran Ancient Volcano of Yogyakarta - Sekarsih, Fitria Nuraini; Mustopa, Ali; Cahyono, Ari; Kukuh, Kukuh (Faculty of Geography, Universitas Gadjah Mada, 2024)
Place naming of a local area is closely related to geographic elements. Local names can also be used as a cultural identity and natural condition of a region. Nglanggeran Ancient Volcano (AV) area has local name elements highly influenced by those conditions. It is an interesting study material where a three-dimensional (3D) model can contribute as a medium to collect the place naming traces (toponym) in this area through participatory mapping. Participatory mapping, usually using 2D models in the form of sketches or maps, will be a separate story in interactive 3D media usage resulting from the photogrammetry process. It is expected that the media be able to show the geographical appearance of the Nglanggeran A.V area more clearly, such as geomorphology, geology, vegetation, hydrology, and even local culture, and contribute unexplored information. The results of participatory mapping in toponym collection are expected to be a medium that organizes the place naming of a local area into a complete database, along with the origin of the place names. It is also proposed that the results of participatory mapping through the 3D model be a means of preserving local culture in the Nglanggeran A.V area, making it more familiar to local residents and tourists.